Manajemen Konstruksi Analisa Keterlambatan Proyek RSUD Kalideres Jakarta Barat - Dadang Malik Darmaji; Muhrojin (edujavare, 2023)
In project implementation, control is needed to avoid errors at the time of implementation, there are three things that need to be considered in the control, namely to be considered in the control, namely: cost, time and quality in accordance with the plan. But in reality, delays in project completion project often occurs because one of the three components is not met. fulfilled. The purpose of this study was to determine the effect of delays in construction of the Kalideres Regional General Hospital in terms of cost, time and quality